An extracellular matrix graft (Oasis® wound matrix) for treating full-thickness pressure ulcers: A randomized clinical trial. Issue 1 (February 2019) - Brown-Etris, Marie; Milne, Catherine T.; Hodde, Jason P.
Abstract: Aim: The purpose of the study was to evaluate clinical safety and effectiveness of Oasis ® Wound Matrix as a treatment for full-thickness pressure ulcers and compare it to Standard Care. Methods: A total of 130 adults with Stage III or Stage IV pressure ulcers were randomly assigned, received either multiple topical treatments of SIS plus standard care (n = 67), or standard care alone (n = 63), and were subsequently evaluated. Ulcer size was determined at enrollment and weekly throughout treatment. Healing was assessed at each visit for a period of up to 12 weeks, with incidence of complete healing and 90% reduction in ulcer area being the primary outcome measures. Results: The proportion of complete healing in the SIS group was 40% as compared to 29% in the standard of care group (p = 0.111); the percentage of patients having a 90% reduction in ulcer surface area was 55% in the SIS group versus 38% in the standard of care group (p = 0.037). Conclusions: The results of this study suggest that within the setting of a comprehensive wound care program, weekly treatment of chronic pressure ulcers with SIS wound matrix increases the incidence of 90% reduction in wound size versus standard of care alone. Highlights: An extracellular (small intestinal submucosa, SIS) wound matrix made from porcine collagen is described. The SIS wound matrix was compared to Standard of Care for treating full-thickness pressure ulcers. The proportion of complete healing in the SIS wound matrix group was higher than the Standard of Care group.